Implementation of the SMED tool for continuous improvement in a process of format exchange in the tissue paper industrial plant: A Bibliometric analysis (Research, Society and Development, 2019)
The tissue industry, over the decades, has shown remarkable growth, which can be explained, for the most part, by the increase of consumer goods for hygiene in developing countries, such as Brazil. The evolution of the market has made it even more competitive and, for companies, it is necessary to assume bold models of management capable of promoting productivity increase with cost reduction, for example with the adoption of SMED (Single Minute Exchange of Die) in one step of production: programmed format change in tissue conversion unit. Thus, this study had as main objective to carry out a bibliometric revision on the subject, in order to map pertinent literature and to ascertain the studies, countries and authors with greater scientific relevance. The database used for bibliometric review was the Web of Science® (WoS). From the results of the research carried out in September 2018, a bank of 10 articles was constructed, observing a large number of publications, 171 in all, on the SMED tool applied in continuous improvement in processes of format change in industrial plants. The countries with the largest number of publications on the subject are Italy, Poland and Turkey and the year the most published on the application of SMED in industries was 2016 and 2017. This highlights the relevance of research on SMED implementation, in addition to In addition, the frequent attempt to propose new methods for reducing the times of format change in industries indicates that there is still a field of research to be explored.